Correspondence between healthcare professionals: an evaluation of a medical student workshop on the importance of the discharge letter - Jiwa, Moyez; Freeman, J.; Tanner, S. (Radcliffe Medical Press Ltd, 2006)
What is already known in this area: Letters from hospital specialists to a patient's GP promote informational continuity of care. There are no benchmarks for the quality of letters from specialists to GPs. Medical students are seldom taught how to correspond with professional colleagues. What this work adds: The majority of students recognise the value of sharing comprehensive information across the interface between primary care and secondary care. Almost one in five students retains the view that discharge summaries do not affect care provided by a GP. Some students believe it is defensible to be rude about patients in discharge letters. Suggestions for future research: Those students who hold questionable views must be identified and offered a tailored educational experience if they are to adopt helpful attitudes.